Recent developments in 2D positive systems theory - Fornasini, Ettore; Valcher, Maria Elena (Zielona Góra: Uniwersytet Zielonogórski)
Two-dimensional (2D) positive systems are 2D state space models whose variables take only nonnegative values and, hence, are described by a family (A, B, M, N, C, D) of nonnegative matrices. In the paper, the notions of asymptotic and simple stability, corresponding to an arbitrary set of nonnegative initial conditions, are introduced and related to the spectral properties of the matrix sum A + B.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka